The Joy of hate : how to triumph over whiners in the age of phony outrage - Gutfeld, Greg (Crown Forum, 2012)
From the irreverent star of Fox News's "Red Eye "and "The Five," hilarious observations on the manufactured outrage of an oversensitive, wussified culture of artificial tolerance.